Cut Bank - Shakman, Matt; Patino, Roberto; Therrell, Matthew; Hemsworth, Liam, 1990-; Palmer, Teresa, 1986-; Thornton, Billy Bob; Malkovich, John; Lions Gate Entertainment (Firm) (Santa Monica, California : Lionsgate, 2015)
Looking to leave his sleepy town of Cut Bank, Dwayne McLaren hatches a get-rich scheme to get himself out. But when Dwayne's plan backfires and he's swept into a murder investigation led by the local sheriff, he discovers that Cut Bank is a Small town full of deadly surprises.
Special features: Deleted scenes; Extended scenes; Audio commentary with director; "Bad Karma: life in Cut bank" featurette.
Liam Hemsworth, Teresa Palmer, Billy Bob Thornton, John Malkovich, Bruce Dern, Oliver Platt.
MPAA rating: R; for violence and language.
DVD, widescreen presentation; 5.1 Dolby Digital; 5.1 DTS-HD.
English dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Criminal investigation -- Drama; Murder -- Drama; Small cities -- Drama; Video recordings for the hearing impaired; Feature films